THE USE OF VIDEO AS A PEDAGOGIC TOOL FOR THE TRAINING OF PERIOPERATIVE NURSES: A LITERATURE REVIEW - Vigeant, Danielle; Lefebvre, Hélène; Reidy, Mary (Operating Room Nurses Association of Canada Journal, 2008)
This review of the literature considers the use of video as a pedagogic tool (teaching instrument) for the training of new perioperative nurses. The literature review seeks to address the question of which usage of the video medium can be integrated into the education of new OR nurses. Kolb’s model of experiential learning, whereby knowledge is acquired by transforming experience into new ways of thinking and behaviours, is the theoretical framework used to analyze the pertinent literature. The selected articles were obtained from the following search engines: CINAHL, ERIC and PSYCH INFO. In addition, articles were obtained from experts in the clinical field. The reviewed literature can be classified into three main categories: the use of video to demonstrate content; the use of video for self-analysis; and the integration of video in to multimedia teaching programs.